The status of the Kurdistan Region-Iraq in the strategy of the united states of America: Iraq as a case study (2003-2021) - Sultan, Saood; Ali, Omran (Humanities Journal of University of Zakho, 2024)
This study aims to elucidate and analyze the role of the Kurdistan Region – Iraq in the strategy of the United States of America in the Middle East, particularly in Iraq, between 2003 and 2021. To achieve this, the study examines the strategic objectives of the United States towards Iraq since 2003, focusing on the promotion of democracy and the transformation of Iraq from a dictatorship to a democracy, as well as the war on terrorism, especially following the emergence of the Islamic State in Iraq in 2014. Specifically, the study investigates the Kurdistan Region – Iraq's consistent position in the US strategy and its role in achieving US strategic objectives in Iraq. It argues that since 2003, the Kurdistan Region – Iraq has played a crucial role in fulfilling US strategic goals in Iraq, whether in eliminating the dictatorial regime to promote democracy or in combating terrorism, particularly the Islamic State. By analyzing US strategic goals in Iraq and the Kurdistan Region's contribution, this study concludes that although the Kurdistan Region is a non-state actor, it has occupied a significant position in US strategy towards Iraq and the wider region, serving as a pivotal factor in promoting democracy and combating terrorism. However, the sustainability of this position is contingent upon the evolving political, security, and regional dynamics, as well as the ongoing strategic interests of the United States in Iraq and the broader region.